Role of hydrogen sulfide in early blood-brain barrier disruption following transient focal cerebral ischemia. - Zheng Jiang; Chun Li; Morganne L Manuel; Shuai Yuan; Christopher G Kevil; Kimberly D McCarter; Wei Lu; Hong Sun (PLoS ONE)
We determined the role of endogenous hydrogen sulfide (H2S) in cerebral vasodilation/hyperemia and early BBB disruption following ischemic stroke. A cranial window was prepared over the left frontal, parietal and temporal cortex in mice. Transient focal cerebral Ischemia was induced by directly ligating the middle cerebral artery (MCA) for two hours. Regional vascular response and cerebral blood flow (CBF) during ischemia and reperfusion were measured in real time. Early BBB disruption was assessed by Evans Blue (EB) and sodium fluorescein (Na-F) extravasation at 3 hours of reperfusion. Topical treatment with DL-propargylglycine (PAG, an inhibitor for cystathionine γ-lyase (CSE)) and aspartate (ASP, inhibitor for cysteine aminotransferase/3-mercaptopyruvate sulfurtransferase (CAT/3-MST)), but not O-(Carboxymethyl)hydroxylamine hemihydrochloride (CHH, an inhibitor for cystathionine β-synthase (CBS)), abolished postischemic cerebral vasodilation/hyperemia and prevented EB and Na-F extravasation. CSE knockout (CSE-/-) reduced postischemic cerebral vasodilation/hyperemia but only inhibited Na-F extravasation. An upregulated CBS was found in cerebral cortex of CSE-/- mice. Topical treatment with CHH didn't further alter postischemic cerebral vasodilation/hyperemia, but prevented EB extravasation in CSE-/- mice. In addition, L-cysteine-induced hydrogen sulfide (H2S) production similarly increased in ischemic side cerebral cortex of control and CSE-/- mice. Our findings suggest that endogenous production of H2S by CSE and CAT/3-MST during reperfusion may be involved in postischemic cerebral vasodilation/hyperemia and play an important role in early BBB disruption following transient focal cerebral ischemia.